A Simplified Model for Dynamic Response Analysis of Framed Self-Centering Wall Structures under Seismic Excitations - Xiaobin Hu; Chen Lu; Xiaoqing Zhu (Shock and Vibration, 2019)
This paper presents a simplified model for dynamic response analysis of the framed self-centering wall (FSCW) structure under seismic excitations. In the analysis model, the frame is equivalent as a single-degree-of-freedom system and collaborates with the self-centering (SC) wall to resist lateral loads. By way of pushover analysis of a typical FSCW structure, the proposed analysis model is validated by comparing the analysis results with those obtained from the finite element analysis method. Using the analysis model, motion equations of the FSCW structure under seismic excitations are established and solved through numerical simulations. Finally, a comprehensive parametric study is conducted to investigate the effects of a variety of design parameters on seismic responses of the FSCW structure. It shows that improving the yield force or elastic stiffness of the frame can help greatly lessen seismic responses of the FSCW structure in terms of the rotation angle of the SC wall.